Diseases threatening banana biodiversity in Uganda - Tushemereirwe, Wilberforce K.; Kangire, A.; Kubiriba, Jerome; Nakyanzi, M.; Gold, Cliford S. (2004)
Banana (Musa spp.) is the most important food crop in Uganda as indicated by consumption rate, annual production (9.5 M t ha-1) and agricultural land committed to the crop. This level of productivity (6.3 t ha-1 yr-1) is extremely low when compared to the yields obtained on station and well-managed plantations (60 t ha-1 yr-1). Previous diagnostic studies attributed the low productivity to diseases, pests, soil fertility decline, limited post harvest utilisation options and socioe-conomic problems. The susceptibility to pests and diseases is largely attributed to a low genetic base of banana in Uganda. Recent on station and on-farm studies suggest the major diseases threatening banana biodiversity in Uganda include: 1)Black sigatoka which severely affects all East African Highland (EA-AAA) banana cultivars and a range of introduced genotypes; 2) Fusarium wilt which affects several introduced genotypes though all EA - AAA bananas are resistant; 3) Banana streak virus causing different levels of infection on all types of banana cultivars; and 4) Banana bacterial wilt, a recent outbreak affecting all types of banana in Mukono and Kayunga districts (central Uganda). This paper illustrates the potential threat posed by the above diseases to Musa biodiversity in Uganda and highlights some of the recent studies undertaken to control the diseases.